Answer:
x = -3, y = -7
x = 3, y = 11
Explanation:
Given that two equations;
y = x² + 3x − 7 ---------------- (1)
3x − y = −2 -----------------------(2)
Solve equation (2) for y
y = 3x + 2
Now plug the value of y into the equation (1)
y = x² + 3x − 7
3x + 2 = x² + 3x - 7
Write it in standard quadratic form.
x² + 3x - 3x - 7 - 2 = 0
x² - 9 = 0
x² = 9
take square root both the side
x = ± 3
Now find the value of y
put x = 3 into the equation (2)
3x - y = -2
3(3) - y = -2
y = 11
So, at x = 3, y=11
Now x = -3
3(-3) - y = -2
y = -7
At x = -3 , y = -7
That's the final answer.